An examination of the effects of gentle teaching on people with complex learning disabilities and challenging behaviour. - Cullen, C; Mappin, R (British Journal of Clinical Psychology, 1998)
This study was conducted to investigate the efficacy of gentle teaching when compared with individual educational programming (IEP) for a group of people with complex learning disabilities and challenging behaviour. An A-B design was used, in which gentle teaching was introduced as an addition to the IEP procedures already in place. Other designs, such as reversal, multiple baseline or group comparisons would have been impractical in this clinical setting. Thirteen students and seven staff were observed, using a hand-held computer for direct observations, and video-recordings for measures of interaction. Staff attitudes to gentle teaching and to the IEP system were also assessed. The intervention was systematic workshop-based training in gentle teaching for all staff. Measures were taken pre-intervention for 13 weeks and post-intervention for 23 weeks. Approximately 45 hours of direct observational data and over 50 hours of video-recording were analysed. We found very few effects of gentle teaching. Wherever there were differences between gentle teaching and IEP these were in favour of gentle teaching, although they were generally relatively minor in terms of clinical (rather than statistical) significance. Inter-rater reliabilities were generally poor, although the figures for those categories where there was a difference between gentle teaching and IEP were amongst the most respectable. Gentle teaching did not have a major impact on staff behaviour, and no discernible effect on student behaviour, but it did not lead to poorer interactions and may be a useful adjunct to more structured approaches such as individual educational programming.